2006
DOI: 10.1271/bbb.70.746
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti-Juvenile Hormone Activity of Ethyl 4-(2-Aryloxyhexyloxy)benzoates

Abstract: A series of ethyl 4-(2-aryloxyhexyloxy)benzoates was prepared and tested for their activity to induce precocious metamorphosis in larvae of the silkworm. Phenyl analog 5 showed activity comparable to that of the 6-methyl-3-pyridyl analog reported as a novel anti-JH agent. The activity of 5 could be fully counteracted by methoprene, a JH agonist. The ethoxycarbonyl group of 5 was essential for its activity.Key words: anti-juvenile hormone; precocious metamorphosis; silkwormThe juvenile hormone (JH) is involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Riddiford et al have reported that ETB acted as a partial antagonist in the Manduca epidermis at the target-tissue level. 7) As previously reported, 3,4) in our bioassay using 24-hr-old 3rd instar larvae of B. mori, ETB at 1 mg induced precocious pupation in only 10% and no activity was observed at higher doses of 10 mg and 40 mg, while compounds 1 and 2 induced precocious metamorphosis even at high doses. ETB clearly acts as a JH agonist to counteract the effect of allatectomy, the induction of precocious metamorphosis, in a dose-dependent manner.…”
supporting
confidence: 79%
“…Riddiford et al have reported that ETB acted as a partial antagonist in the Manduca epidermis at the target-tissue level. 7) As previously reported, 3,4) in our bioassay using 24-hr-old 3rd instar larvae of B. mori, ETB at 1 mg induced precocious pupation in only 10% and no activity was observed at higher doses of 10 mg and 40 mg, while compounds 1 and 2 induced precocious metamorphosis even at high doses. ETB clearly acts as a JH agonist to counteract the effect of allatectomy, the induction of precocious metamorphosis, in a dose-dependent manner.…”
supporting
confidence: 79%
“…Among them, the phenyl analog 4 showed activity comparable to those of 2 and 3, suggesting that 6-methyl-3-pyridyl moiety is not significant for activity. 10) In this series of compounds, the introduction of a methyl or chloro substituent on the benzene ring did not increase activity. In the alkyl 4-(2-phenoxyhexyloxy)benzoate series, only methyl and ethyl esters showed precocious metamorphosis-inducing activity.…”
Section: Synthesis and Biological Activity Of Novel Anti-juvenile Hormentioning
confidence: 71%
“…The n-pentyl analog 7 had almost the same level of activity as 6 and was most effective at treatment of 1 mg. The n-hexyl (8) and benzyl (9) analogs showed lower activity at low doses in comparison with those of 6 and 7. Only compounds 6 and 7 showed some precocious metamorphosis-inducing activity at a very low dose of 0.1 mg.…”
Section: Synthesismentioning
confidence: 92%
“…By modifying the structure of ETB, we have recently found that ethyl 4-[4-methyl-2-(6-methyl-3-pyridyloxy)pentyloxy]-benzoate (1) 7) and ethyl 4-(2-phenoxyhexyloxy)benzoate (2) 8) showed stronger precocious metamorphosis-inducing activity than ETB against B. mori larvae (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%